Analisis Penataan Gudang dan Tumpukan Pada Gudang Barang Setengah Jadi PT.Integra Indocabinet.Tbk - Davin Herdiansyah Putra; Noval Sigit Nurdianto; Khoirul Yanuar Rizqi; Putu Eka Karunia Dewi (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The main objective of arranging the warehouse layout is to find the most appropriate method so that the movement of goods in the warehouse runs smoothly. Apart from that, the aim of setting the warehouse layout is also to maximize the warehouse area so that the costs of handling activities remain low. Stacks of goods in the warehouse are stacked with a maximum height of 700 cm and above or approximately 7 items stacked in one pile. If these items continue to be stacked using 7 stacks and above, it can cause many defects to occur. This defect occurs because there are too many items piled up. The pile of items should be stacked with a maximum of 5 piles and above. Therefore, defects that occur can cause delays in delivery times and result in large costs experienced due to these defects